Seasonal signatures in the physical properties of a tropical estuary in the Central America Pacific - Brenes, C.L. (2013)
A hydrographic survey was carried out in the Jaltepeque estuary in the Pacific coast of El Salvador. From September 2005 to March 2006, 10 sampling stations were occupied to measure temperature, salinity, dissolved oxygen and turbidity. Surface temperatures between 27 and 30.6 °C were observed during the survey, with extreme temporal variations close to 3°C. Minimum temperatures occur in October and February. Surface salinity shows a clear seasonal cycle, with values greater than 30o/oo during the dry months over virtually the whole body of water, while in the rainy season (September-October), salinity ranges from 2 o/oo to 22o/oo. Maximum surface oxygen and turbidity were observed from October to December and minimum values in March. During the dry months (December-March), turbidity levels are low throughout the estuary. The vertical termohaline fields show a stratified estuary during the rainy season. This stratification breaks down during the dry season and the system behaves as well-mixed estuary. Dissolved oxygen did not show significant vertical stratification during the survey.